Estudo de perfil de dissolução dos medicamentos de referência, genérico e similar contendo cefalexina na forma farmacêutica cápsula - Chorilli, Marlus [UNESP]; Souza, A. A.; Corrêa, F.; Salgado, Hérida Regina Nunes [UNESP] (My University, 2010)
With recent advances in technology and research into drug delivery, the modernization of tests and greater emphasis on the predictability of therapeutic effect by means of in vitro tests, the dissolution test and the study of dissolution profiles are gaining more and more importance. Though introduced initially as a way of characterizing the release profile of poorly soluble drugs, dissolution tests are currently part of pharmacopoeial monographs on almost all the oral solid pharmaceutical forms. The objective of this study was to determine the dissolution profile (percent drug dissolved versus time) of the pioneer brand, generic and similar pharmaceutical capsules containing 500mg cephalexin. Three pharmaceutical brands (reference, generic and similar) were subjected to the dissolution test and in vitro dissolution profiles were recorded. From the results of the dissolution test, it was concluded that the samples met the acceptance criterion, as no difference was observed in the percentage of the drug dissolved in a standard time. The dissolution profile indicated that this medicine, in this pharmaceutical form, dissolves readily (85% of the drug dissolved in 15 minutes) and the curves showed great similarity, suggesting that the 3 brands are pharmaceutically equivalent.

Com o avanço da tecnologia e das pesquisas envolvendo liberação de fármacos, modernização de testes e maior ênfase da previsibilidade de efeitos terapêuticos por meio dos testes in vitro, os testes de dissolução e os estudos de perfis de dissolução têm ganhado cada vez mais importância. Apesar de terem sido introduzidos inicialmente como uma forma de caracterizar o perfil de liberação de fármacos pouco solúveis, atualmente os testes de dissolução fazem parte das monografias de quase todas as formas farmacêuticas sólidas orais. Este trabalho teve como objetivo estudar o perfil de dissolução (porcentagem de fármaco dissolvido versus tempo) dos medicamentos de referência, genérico e similar contendo cefalexina 500 mg na forma farmacêutica de cápsulas. Foram analisadas três especialidades farmacêuticas (referência, genérico e similar), os quais foram submetidos ao teste de dissolução e perfil de dissolução in vitro. Os resultados obtidos no teste de dissolução permitem concluir que as amostras encontraram-se de acordo com as especificações e o perfil de dissolução deste medicamento, nesta forma farmacêutica, é considerado de dissolução rápida (85% de fármaco dissolvido em 15 minutos). Portanto, existe uma grande semelhança entre as curvas obtidas, o que sugere que se trata de equivalentes farmacêuticos.
Study of dissolution profile of the pioneer brand name, generic and similar brand name pharmaceutical products containing cephalexin in the form of capsules
Keywords: Cephalexin; Dissolution profile; Generic medicine; Reference medicine; Similar medicine; cefalexin; generic drug; capsule endoscope; drug delivery system; drug dosage form; drug release; drug research; drug solubility; in vitro study; medical literature